Social Realism in Jaiprakash Kardam’s Novel Chhappar : जयप्रकाश कर्दम के ‘छप्पर’ उपन्यास में सामाजिक यथार्थ - Badetia , Shweta; Panwar, Kailash (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Through his novel Chhappar, Jaiprakash Kardam attempts to portray the story of the most marginalized section of society. Set against the backdrop of a small village named Matapur in Western Uttar Pradesh, the protagonist of this novel is Chandan, who moves from the village to the city for his education. His parents dream of seeing him become a high-ranking officer. Upon arriving in the city, Chandan becomes aware of the harsh realities of urban life. His primary objective is to awaken the Dalit community, which has been trapped for centuries in ignorance and backwardness. While studying in college, he simultaneously runs a school and teaches young children himself. He believes that education is the most effective and powerful weapon to win the battle against the disparities prevailing in life and society. Abstract in Hindi Language: जयप्रकाश कर्दम ने ’छप्पर’ उपन्यास के माध्यम से समाज के सबसे पिछड़े वर्ग की कहानी कहने की कोशिश की है। पश्चिमी उत्तर प्रदेश के एक छोटे से गाँव मातापुर की पृष्ठभूमि पर लिखे गए इस उपन्यास का कथा नायक चंदन है, जो गाँव से शहर पढ़ने जाता है। उसके माता-पिता की इच्छा है कि वह कोई बड़ा अधिकारी बने। शहर पहुँचकर चंदन को शहर की सच्चाई का पता चलता है। चंदन का उद्देश्य है कि वह सदियों से अज्ञानता और पिछड़ेपन की गति में पड़े हुए दलित समाज को जगाए। वह कॉलेज में पढ़ते हुए भी स्कूल चलाता है और छोटे बच्चों को स्वयं पढ़ाता है। वह जानता है कि जीवन और समाज में व्याप्त विसंगतियों के खिलाफ लड़ाई जीतने के लिए शिक्षा सबसे मारक और शक्तिशाली शस्त्र है। Keywords: दलित समाज, सहानुभूति, स्वानुभूति, गुलामगिरी, अल्पसंख्यक, अतिवाद।